2012
DOI: 10.1016/j.aller.2011.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Study of wheezing and its risk factors in the first year of life in the Province of Salamanca, Spain. The EISL Study

Abstract: In the province of Salamanca, one third of the infants studied suffered wheezing in the first year of life. Infants exclusively breastfed for less than three months; attending a nursery; having suffered eczema; or with an asthmatic mother showed significantly more wheezing than the rest. Wheezing proved recurrent in 11.9% of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0
14

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
3
4
0
14
Order By: Relevance
“…Prevalence of wheezing ever in infants in our study was 31.2%, similar prevalence compared to others EISL studies conducted in Spain, in the city of Salamanca, which found 32.3% (14) and in Netherlands, 28.5% (7), but less prevalence than in Latin America countries, where mean prevalence was 47.3% (15). Prevalence of recurrent wheezing was 12.3%, similar to the other Spanish EISL study (14), but lower than other European and Latin American studies (7,9).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Prevalence of wheezing ever in infants in our study was 31.2%, similar prevalence compared to others EISL studies conducted in Spain, in the city of Salamanca, which found 32.3% (14) and in Netherlands, 28.5% (7), but less prevalence than in Latin America countries, where mean prevalence was 47.3% (15). Prevalence of recurrent wheezing was 12.3%, similar to the other Spanish EISL study (14), but lower than other European and Latin American studies (7,9).…”
Section: Discussionsupporting
confidence: 90%
“…In our study infant eczema presented a higher risk for both wheezing ever and recurrent wheezing. This relation was also found in another EISL study (14), although is not a general finding, suggesting it affects some populations. Garcia-Marcos et al (21) found that infant eczema was a risk factor for pneumonia in infants, which suggest a role between eczema and the development of other risk factors which lead to wheezing.…”
Section: Discussionsupporting
confidence: 73%
“…Exposure to cigarette smoke, both in the prenatal period and after birth, was associated with the risk of wheezing in infants and preschool children in several studies. 1,17,25 A meta-analysis observed that prenatal or postnatal exposure increased the risk of incidence of wheezing by 30% to 70%, mainly in children younger than two years, stressing that parental smoking prevention is crucial for asthma prevention. 7 The present study demonstrated that living in a moderately polluted environment was a risk factor for wheezing in the first year of life, similar to that observed in other studies.…”
Section: Variablesmentioning
confidence: 99%
“…Annenin gebelikte sigara içmesi ve postnatal pasif sigara içimi çocukluk çağındaki tekrarlayan hışıltı atakları için ve persistan bronşiyal obstrüksiyon için güçlü bir risk faktörüdür (19,20). Lødrup Carlsen (21) 1233 çocuğu içeren çalışmasında, intrauterin sigaraya maruz kalan çocukların doğumdaki akciğer fonksiyonlarının önemli derecede azaldığını, ayrıca pasif sigara içimine maruz kalan sağlıklı çocuklarda serum ECP düzeyinin arttığını göstermiştir.…”
Section: Discussionunclassified
“…Hasta gruplarındaki oranlar kontrol grubuna göre daha yüksek olmakla birlikte aradaki fark istatistiksel olarak anlamlı değildi. Maternal ve/veya postnatal pasif sigara içiminin her iki hışıltı grubunda yüksek olması gebelikte ya da postnatal pasif sigara içiminin hışıltı atakları için risk oluşturduğu görüşüyle uyumludur (19,20). Ancak istatistiksel olarak anlamlı bir farkın saptanamamasının hasta sayısının az olmasından kaynaklanabileceği düşünülmüştür.…”
Section: Discussionunclassified